A case of pleomorphic adenoma on the anterior part of the tongue. Issue 5 (September 2022) - Kogi, Shintaro; Ogawa, Atsushi; Ikeda, Yunosuke; Takahashi, Noriaki; Takeda, Yasunori; Yamada, Hiroyuki
Abstract: Pleomorphic adenoma, also known as a mixed tumor, is the most common benign tumor of the major and minor salivary glands. Pleomorphic adenomas rarely occur at the anterior aspect of the tongue, and several cases have been reported. An 87-year-old man presented with an encapsulated mass, measuring approximately 40 mm in diameter, on the anterior part of the tongue. Computed tomography showed a well-defined mass with a heterogeneous density and less prominent enhancement on the anterior part of the tongue. Based on the clinical diagnosis of benign tumor of the tongue, the mass was removed via complete oral excision under intravenous sedation. The excised specimen was diagnosed as a pleomorphic adenoma. It was presumed to be a tumor derived from the Blandin-Nuhn gland. This was a rare case of pleomorphic adenoma occurring on the anterior aspect of the tongue.